Innovaciones tecnológicas en agroecosistemas de pitahaya (Selenicereus undatus) en zonas tropicales del Ecuador - Gavilanez Palma, Gustavo Daniel (2024)
This study seeks to explain the technological innovations in dragon fruit cultivation as they transform the agricultural industry through increased production efficiency, productivity and sustainability. Advanced smart irrigation and climate control systems are used in greenhouses to optimize water use and provide optimal growing conditions. In addition, precision agriculture, using drones and sensors, allows detailed monitoring of crops and early detection of pests and diseases, allowing for a rapid response.The use of innovations in the automation of agricultural tasks and the implementation of post-harvest technologies guarantee product quality and freshness, while data management and analysis help make informed decisions to continually improve agricultural practices. These innovations are making dragon fruit cultivation more efficient and profitable, while reducing its environmental impact.